Development of an omnidirectional rotating Compton camera for imaging 177Lu radioactive contamination. - Hikari Tsukamoto; Hiroshi Muraishi; Ryoji Enomoto; Hideaki Katagiri; Mika Kagaya; Takara Watanabe; Takahiro Mizoguchi; Masaya Fukumoto; Daisuke Kano; Yusuke Watanabe; Kazuya Sakaguchi; Hiromichi Ishiyama (PLoS ONE)
In this study, we developed an omnidirectional rotating Compton camera that was capable of imaging low-level radioactive contamination caused by 177Lu-oxodotreotide, a novel radiopharmaceutical that has recently been attracting attention in nuclear medicine. The detector employs a compact design that comprises only six scintillator crystals mounted on a motorized rotating stage. By optimizing the crystal type and size, and optimizing the interval between crystals, the detector is able to adapt to a wide range of environmental conditions, including observable gamma-ray energies, dose rates, and angular resolution. Monte Carlo simulations using Geant4 were conducted to optimize the configuration of the detector. Based on the results of the simulation, a prototype detector using six 3.5 cm cubic [Formula: see text] crystals was developed for visualizing 177Lu-contaminated sites. The experimental results demonstrated that the detector could successfully visualize an unsealed 177Lu -oxodotreotide source with high sensitivity without being affected by gamma rays from 99TC, which is also present in nuclear medicine facilities. The developed rotating Compton camera technology is anticipated to serve as a reliable environmental monitoring tool in nuclear medicine facilities. Through its ability to rapidly detect radioactive contamination, this detector has the potential to reduce the radiation exposure risks for both medical professionals and the general public.